APPLICATION OF PEPTIDES FOR THE MANUFACTURE OF COSMETIC CREAMS - MOLCHANOVA, KATERINA; ANDREYEVA, OLGA; PERVAIA, NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Cosmetic creams are considered one of the most common types of cosmetic products. This is due to their preventive and therapeutic properties, ease of consumption and affordability. The largest part of cosmetic facial skin care creams is created on the basis of emulsions, which can be explained by the ability of the latter to combine oil and water phases, the possibility of introducing various active ingredients and good consumer properties. Particular attention is drawn to products that have not only a cosmetic effect, but also have special properties such as regenerating, antibacterial, wound healing ability. To create products that have a more effective effect on the skin, the search for components and technological methods that can provide this is relevant.Recent advances in pharmaceutical, bio- and chemical technology have led to the development of innovative cosmeceuticals that use peptides to improve skin condition. The long-term benefits of these products have not yet been adequately assessed, but a review of the literature indicates a growing body of evidence to support their use. This is achieved due to the inclusion in the composition of emulsion cosmetic creams of low molecular weight peptides obtained by hydrolysis of proteins of plant origin, marine animals, as well as agents that enhance their penetration into the skin in the form of chemical enhancers and needle patches. At the same time, it should be noted that the use of natural resources for the production of bioactive peptides is not enough to meet the growing demands of consumers. To solve this problem, various biotechnological tools and processes for the synthesis of bioactive peptides are used. The main requirements for the created peptide compositions are their physical and chemical stability, compatibility with the skin and its components, and effective action.
Keywords: cosmetic creams; peptides; technology; properties